Low cost tips for tip-enhanced Raman spectroscopy fabricated by two-step electrochemical etching of 125 µm diameter gold wires - Foti, Antonino; Barreca, Francesco; Fazio, Enza; D’Andrea, Cristiano; Matteini, Paolo; Maragò, Onofrio Maria; Gucciardi, Pietro Giuseppe (Beilstein Journal of Nanotechnology, 2018)
Tip-enhanced Raman spectroscopy (TERS) has become a well-applied technique for nanospectroscopy, allowing for single molecule sensitivity with sub-nanometer spatial resolution. The demand for efficient, reproducible and cost-effective probes for TERS is increasing. Here we report on a new electrochemical etching protocol to fabricate TERS tips starting from 125 µm diameter gold wires in a reproducible way. The process is reliable (50% of the tips have radius of curvature <35 nm, 66% <80 nm), fast (less than 2 min) and 2.5 times cheaper than the etching of standard 250 µm diameter wires. The TERS performance of the tips is tested on dyes, pigments and biomolecules and enhancement factors higher than 105 are observed. TERS mapping with a spatial resolution of 5 nm is demonstrated.
Keywords: amyloid; enhanced spectroscopy; gold tips; plasmonics; TERS

(untitled) - Stöckle, R. M.; Suh, Y. D.; Deckert, V.; Zenobi, R. (Chem. Phys. Lett., 2000)

(untitled) - Anderson, M. S. (Appl. Phys. Lett., 2000)

(untitled) - Hayazawa, N.; Inouye, Y.; Sekkat, Z.; Kawata, S. (Opt. Commun., 2000)

(untitled) - Pettinger, B.; Picardi, G.; Schuster, R.; Ertl, G. (Electrochemistry, 2000)

Principles of Nano-optics - Novotny, L.; Hecht, B. (Cambridge University Press, 2012)

(untitled) - Novotny, L.; van Hulst, N. (Nat. Photonics, 2011)

(untitled) - Shi, X.; Coca-López, N.; Janik, J.; Hartschuh, A. (Chem. Rev., 2017)

(untitled) - Yang, Z.; Aizpurua, J.; Xu, H. (J. Raman Spectrosc., 2009)

(untitled) - Kottmann, J. P.; Martin, O. J. F.; Smith, D. R.; Schultz, S. J. (J. Microsc. (Oxford, U. K.), 2001)

(untitled) - Barbry, M.; Koval, P.; Marchesin, F.; Esteban, R.; Borisov, A. G.; Aizpurua, J.; Sánchez-Portal, D. (Nano Lett., 2015)

(untitled) - Zhang, W.; Yeo, B. S.; Schmid, T.; Zenobi, R. (J. Phys. Chem. C, 2007)

(untitled) - Sonntag, M. D.; Klingsporn, J. M.; Garibay, L. K.; Roberts, J. M.; Dieringer, J. A.; Seideman, T.; Scheidt, K. A.; Jensen, L.; Schatz, G. C.; Van Duyne, R. P. (J. Phys. Chem. C, 2012)

(untitled) - Kharintsev, S. S.; Hoffmann, G. G.; Dorozhkin, P. S.; With, G. d.; Loos, J. (Nanotechnology, 2007)

(untitled) - Pettinger, B.; Ren, B.; Picardi, G.; Schuster, R.; Ertl, G. (Phys. Rev. Lett., 2004)

(untitled) - Hartschuh, A.; Sánchez, E. J.; Xie, X. S.; Novotny, L. (Phys. Rev. Lett., 2003)

(untitled) - Yano, T.-a.; Verma, P.; Saito, Y.; Ichimura, T.; Kawata, S. (Nat. Photonics, 2009)

(untitled) - Steidtner, J.; Pettinger, B. (Phys. Rev. Lett., 2008)

(untitled) - Zhang, R.; Zhang, Y.; Dong, Z. C.; Jiang, S.; Zhang, C.; Chen, L. G.; Zhang, L.; Liao, Y.; Aizpurua, J.; Luo, Y.; Yang, J. L.; Hou, J. G. (Nature, 2013)

(untitled) - Jiang, S.; Zhang, Y.; Zhang, R.; Hu, C.; Liao, M.; Luo, Y.; Yang, J.; Dong, Z.; Hou, J. G. (Nat. Nanotechnol., 2015)

(untitled) - Mauser, N.; Hartschuh, A. (Chem. Soc. Rev., 2014)

(untitled) - Wang, X.; Huang, S.-C.; Huang, T.-X.; Su, H.-S.; Zhong, J.-H.; Zeng, Z.-C.; Li, M.-H.; Ren, B. (Chem. Soc. Rev., 2017)

(untitled) - Sharma, G.; Deckert-Gaudig, T.; Deckert, V. (Adv. Drug Delivery Rev., 2015)

(untitled) - Zhang, Z.; Sheng, S.; Wang, R.; Sun, M. (Anal. Chem., 2016)

(untitled) - Zrimsek, A. B.; Chiang, N.; Mattei, M.; Zaleski, S.; McAnally, M. O.; Chapman, C. T.; Henry, A.-I.; Schatz, G. C.; Van Duyne, R. P. (Chem. Rev., 2017)

(untitled) - Bonhommeau, S.; Lecomte, S. (ChemPhysChem, 2018)

(untitled) - Gucciardi, P. G.; Trusso, S.; Vasi, C.; Patanè, S.; Allegrini, M. (Appl. Opt., 2003)

(untitled) - Hell, S. W. (Science, 2007)

(untitled) - Montgomery, P. C.; Leong-Hoi, A.; Anstotz, F.; Mitev, D.; Pramatarova, L.; Haeberlé, O. (J. Phys.: Conf. Ser., 2016)

(untitled) - Maouli, I.; Taguchi, A.; Saito, Y.; Kawata, S.; Verma, P. (Appl. Phys. Express, 2015)

(untitled) - Huang, T.-X.; Huang, S.-C.; Li, M.-H.; Zeng, Z.-C.; Wang, X.; Ren, B. (Anal. Bioanal. Chem., 2015)

(untitled) - Ren, B.; Picardi, G.; Pettinger, B. (Rev. Sci. Instrum., 2004)

(untitled) - Sasaki, S. S.; Perdue, S. M.; Perez, A. R.; Tallarida, N.; Majors, J. H.; Apkarian, V. A.; Lee, J. (Rev. Sci. Instrum., 2013)

(untitled) - Bonaccorso, F.; Calogero, G.; Di Marco, G.; Maragò, O. M.; Gucciardi, P. G.; Giorgianni, U.; Channon, K.; Sabatino, G. (Rev. Sci. Instrum., 2007)

(untitled) - Taguchi, A.; Hayazawa, N.; Furusawa, K.; Ishitobi, H.; Kawata, S. (J. Raman Spectrosc., 2009)

(untitled) - Kalbacova, J.; Rodriguez, R. D.; Desale, V.; Schneider, M.; Amin, I.; Jordan, R.; Zahn, D. R. T. (Nanospectroscopy, 2015)

(untitled) - Yeo, B.-S.; Zhang, W.; Vannier, C.; Zenobi, R. (Appl. Spectrosc., 2006)

(untitled) - Asghari-Khiavi, M.; Wood, B. R.; Hojati-Talemi, P.; Downes, A.; McNaughton, D.; Mechler, A. (J. Raman Spectrosc., 2012)

(untitled) - Rodriguez, R. D.; Sheremet, E.; Müller, S.; Gordan, O. D.; Villabona, A.; Schulze, S.; Hietschold, M.; Zahn, D. R. T. (Rev. Sci. Instrum., 2012)

(untitled) - Saito, Y.; Murakami, T.; Inouye, Y.; Kawata, S. (Chem. Lett., 2005)

(untitled) - Brejna, P. R.; Griffiths, P. R. (Appl. Spectrosc., 2010)

(untitled) - De Angelis, F.; Das, G.; Candeloro, P.; Patrini, M.; Galli, M.; Bek, A.; Lazzarino, M.; Maksymov, I.; Liberale, C.; Andreani, L. C.; Di Fabrizio, E. (Nat. Nanotechnol., 2010)

(untitled) - Farahani, J. N.; Pohl, D. W.; Eisler, H.-J.; Hecht, B. (Phys. Rev. Lett., 2005)

(untitled) - Fleischer, M.; Weber-Bargioni, A.; Altoe, M. V. P.; Schwartzberg, A. M.; Schuck, P. J.; Cabrini, S.; Kern, D. P. (ACS Nano, 2011)

(untitled) - Fujita, Y.; Walke, P.; De Feyter, S.; Uji-i, H. (Jpn. J. Appl. Phys., 2016)

(untitled) - Eisele, M.; Krüger, M.; Schenk, M.; Ziegler, A.; Hommelhoff, P. (Rev. Sci. Instrum., 2011)

(untitled) - Lopes, M.; Toury, T.; de La Chapelle, M. L.; Bonaccorso, F.; Giuseppe Gucciardi, P. (Rev. Sci. Instrum., 2013)

(untitled) - James, D. F. (J. Fluid Mech., 1974)

(untitled) - Baykul, M. C. (Mater. Sci. Eng., B, 2000)

(untitled) - Wang, X.; Liu, Z.; Zhuang, M.-D.; Zhang, H.-M.; Wang, X.; Xie, Z.-X.; Wu, D.-Y.; Ren, B.; Tian, Z.-Q. (Appl. Phys. Lett., 2007)

(untitled) - Foti, A.; D’Andrea, C.; Bonaccorso, F.; Lanza, M.; Calogero, G.; Messina, E.; Maragò, O. M.; Fazio, B.; Gucciardi, P. G. (Plasmonics, 2013)

(untitled) - Qian, H.; Hsu, S.-W.; Gurunatha, K.; Riley, C. T.; Zhao, J.; Lu, D.; Tao, A. R.; Liu, Z. (Nat. Photonics, 2018)

(untitled) - Mertens, J.; Kleemann, M.-E.; Chikkaraddy, R.; Narang, P.; Baumberg, J. J. (Nano Lett., 2017)

(untitled) - Pettinger, B.; Domke, K. F.; Zhang, D.; Schuster, R.; Ertl, G. (Phys. Rev. B, 2007)

(untitled) - Wang, X.; Braun, K.; Zhang, D.; Peisert, H.; Adler, H.; Chassé, T.; Meixner, A. J. (ACS Nano, 2015)

(untitled) - Carles, R.; Bayle, M.; Benzo, P.; Benassayag, G.; Bonafos, C.; Cacciato, G.; Privitera, V. (Phys. Rev. B, 2015)

(untitled) - Hugall, J. T.; Baumberg, J. J. (Nano Lett., 2015)

(untitled) - Sanders, A.; Bowman, R. W.; Zhang, L.; Turek, V.; Sigle, D. O.; Lombardi, A.; Weller, L.; Baumberg, J. J. (Appl. Phys. Lett., 2016)

Artists’ Pigments - Schweppe, H.; Winter, J. (Madder and Alizarin, 1997)

(untitled) - Chiti, F.; Dobson, C. M. (Annu. Rev. Biochem., 2006)

(untitled) - Cañamares, M. V.; Chenal, C.; Birke, R. L.; Lombardi, J. R. (J. Phys. Chem. C, 2008)

(untitled) - Kudelski, A. (Chem. Phys. Lett., 2005)

(untitled) - Holmgren, A.; Wu, L.; Forsling, W. (Spectrochim. Acta, Part A, 1999)

(untitled) - D’Andrea, C.; Fazio, B.; Gucciardi, P. G.; Giordano, M. C.; Martella, C.; Chiappe, D.; Toma, A.; Buatier de Mongeot, F.; Tantussi, F.; Vasanthakumar, P.; Fuso, F.; Allegrini, M. (J. Phys. Chem. C, 2014)

(untitled) - Tatini, F.; Pugliese, A. M.; Traini, C.; Niccoli, S.; Maraula, G.; Ed Dami, T.; Mannini, B.; Scartabelli, T.; Pedata, F.; Casamenti, F.; Chiti, F. (Neurobiol. Aging, 2013)

(untitled) - Campioni, S.; Mannini, B.; Zampagni, M.; Pensalfini, A.; Parrini, C.; Evangelisti, E.; Relini, A.; Stefani, M.; Dobson, C. M.; Cecchi, C.; Chiti, F. (Nat. Chem. Biol., 2010)

(untitled) - van den Akker, C. C.; Deckert-Gaudig, T.; Schleeger, M.; Velikov, K. P.; Deckert, V.; Bonn, M.; Koenderink, G. H. (Small, 2015)

(untitled) - Deckert-Gaudig, T.; Kurouski, D.; Hedegaard, M. A. B.; Singh, P.; Lednev, I. K.; Deckert, V. (Sci. Rep., 2016)

(untitled) - Kurouski, D.; Deckert-Gaudig, T.; Deckert, V.; Lednev, I. K. (Biophys. J., 2014)

(untitled) - Cleary, J. P.; Walsh, D. M.; Hofmeister, J. J.; Shankar, G. M.; Kuskowski, M. A.; Selkoe, D. J.; Ashe, K. H. (Nat. Neurosci., 2005)

(untitled) - D'Andrea, C.; Foti, A.; Cottat, M.; Banchelli, M.; Capitini, C.; Barreca, F.; Canale, C.; de Angelis, M.; Relini, A.; Maragò, O. M.; Pini, R.; Chiti, F.; et al. (Small, 2018)

(untitled) - Patane, S.; Gucciardi, P. G.; Labardi, M.; Allegrini, M. (Riv. Nuovo Cimento Soc. Ital. Fis., 2004)

(untitled) - Bhattarai, A.; Joly, A. G.; Hess, W. P.; El-Khoury, P. Z. (Nano Lett., 2017)